Reliability interval for a stochastic project network constrained by budget and time. Issue 1 (2nd January 2019) - Lin, Yi-Kuei; Chang, Ping-Chen; Cho, Yun-Ling
Abstract: In a project, duration and cost of activities are stochastic in nature due to uncertainties (natural disaster and human factors). Thus, a project is commonly modeled as a stochastic project network (SPN). For a project manager, it is a duty to manage both efficiency and effectiveness of an SPN. To achieve this goal, this paper develops a procedure to derive project reliability interval for an SPN. The project reliability interval is a performance indicator to assess the probability of project completion under budget and time constraints. Such an indicator provides project manager a quantitative measurement and a qualitative implication to decide a reasonable completion time and budget for an SPN. Quantitative measurement shows the efficiency of budget and time consumption to complete a project; while qualitative implication provides the effectiveness after implementing a project. A practical project of disaster recovery system is utilized to demonstrate how the project reliability interval is applicable in the real life. Sensitivity analysis is further implemented to investigate the project reliability interval under various constraints of project time and budget.